The Effect of Nanochitosan Loaded with Antibiotics on Response of Helicobacter Pylori - Ahmed, Ali; Zbar, Nidhal; Ali, Zainab (Arab Journal for Sciences and Research Publishing, 2016)
A study was conducted to identify the effect of the antibiotics tetracycline and ciprofloxacin as free and loaded on nanochitosan on Helicobacter pylori bacterium isolates causing acute and hemorrhagic stomach ulcer infection in human. Antibiotics sensitivity tests were done by discs and wells techniques. The virulence and growth of these isolates were measured by ammonia production and optical density (OD 575 nm) respectively, under the conditions of presence of free antibiotics and nanochitosan loaded antibiotics. Sensitivity tests showed that each isolates was sensitive to CIP (5µg) more than T (30µg) discs. Scanning electronic microscope images illustrated the formation of spherical structure of nanochitosan as free and loaded with antibiotics. Results of qualitative tests showed a duplication in inhibition zone in the presence of nanochitosan loaded with ciprofloxacin for each of the two isolates after 48 hours compared with free antibiotics. No negligible effect was found for free tetracycline and nanochitosan. Concentrations of produced ammonia were reduced to less than 5 µg/ml for nanochitosan loaded with ciprofloxacin for each of hemorrhage and acute isolates in comparison with a free ciprofloxacin (28.7 µg/ml). A clear change in the pH and color due to the effect of the antibiotic, nanochitosan and ammonia production.